2021
DOI: 10.13170/depik.10.2.20367
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the addition of starry triggerfish (Abalistes stellaris) bone charcoal as a feed supplement to the growth performance and intestinal villi length of nile tilapia (Oreochromis niloticus)

Abstract: Nile tilapia is a freshwater fish that is widely cultivated in Indonesia. During its development, tilapia aquaculture has constraints such as low growth rates. Therefore, it is necessary to add a feed additive to the feed in the form of charcoal. Charcoal is an adsorbent that has high absorption so that the addition of charcoal in the feed can increase the absorption of nutrients of tilapia. A 45-days trial was conducted to determine the percentage of addition of triggerfish bone charcoal (Abalistes stellaris)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 0 publications
0
5
0
3
Order By: Relevance
“…The researchers associated the growth performance of flounder with the availability of macronutrients like protein, leading to a better nutrient build-up in the body. Fish became healthier, their nutritional absorption boosted, and their feed efficiency increased by using charcoal, which has a carbon content of 85–95 %, a large surface area and pores that improved in nutrient absorption and fish growth ( Thaib et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…The researchers associated the growth performance of flounder with the availability of macronutrients like protein, leading to a better nutrient build-up in the body. Fish became healthier, their nutritional absorption boosted, and their feed efficiency increased by using charcoal, which has a carbon content of 85–95 %, a large surface area and pores that improved in nutrient absorption and fish growth ( Thaib et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“… Thaib et al . (2021) evaluated triggerfish bone charcoal (1%, 2%, and 3%) influence on the performance and intestines of 240 Tilapia fingerlings and found that 3% charcoal contributed to enhanced length of intestinal villi up to 71.11 μm from the initial length and higher FCRs with the best feed efficiencies.…”
Section: Discussionmentioning
confidence: 99%
“…The gut structure of fish, including factors such as the length and surface area of the intestine, the thickness of the intestinal wall, and the presence of intestinal folds and microvilli, can significantly impact the digestion and absorption of nutrients from the feed, ultimately affecting FCE and phosphorus retention efficiency [59]. Studies have shown that fish with a higher gut surface area or longer intestine tend to exhibit higher FCE, indicating their enhanced ability to digest and absorb nutrients from the feed [60,61] Moreover, the relationship between FCE and phosphorus pollution in aquaculture is crucial.…”
Section: Relationship Between Fish Gut Structure and Feed Conversion ...mentioning
confidence: 99%